PENGARUH DIFERENSIASI PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK MUSTIKA RATU - Sumarsih (2013)
This study aimed to investigate the effect of product differentiation and brand image on purchase decision on Cosmetic Mustika Ratu. The data used are primary data and data processing performed using SPSS 17.0 Variable studied consisting of product quality, brand image and purchasing decisions. The analysis used to test this study is multiple regression. With the help of SPSS 17.0 sampling method in this study is a non probability sampling with purposive sampling method. The results obtained that the total score of the responses on product differentiation on purchase decisions Mustika cosmetics queen obtained a score of 0.481, while the total score of the total respondents about the brand image on purchase decisions Mustika cosmetics queen obtained a score of 0.514. This shows that there are significant differences in scores were seen from the variable product differentiation and brand image variables on purchase decisions Mustika cosmetics queen. And can be interpreted variable brand image has a greater influence on purchase decisions, when compared with product differentiation